Interdisciplinary Approach to Wordless Novels of the First Half of the 20th Century Research - Dedyukhina, Polina V. (Actual Problems of Theory and History of Art, 2022)
The article deals with the problem of studying such a complex phenomenon in graphic art of the first half of the 20th century, as a wordless novel. Both literature and visual art features, and their aesthetic potential are synthesized in wordless novels. Besides, it was also influenced by silent cinema. A wordless novel, in fact, is an extended graphic series, enclosed in a book form, consisted of a series of images connected by a single narrative. Images form a total artwork which consists of particular elements. It is important that such works do not have a textual basis, the verbal component in them is completely replaced by an image. Combining the features of various types of art, this genre, at the same time, does not apply to any of them. The most comprehensive study of it is possible only by combining of various approaches. Possible ways to study such pieces of art are presented in the article.
Keywords: wordless novel; novel in woodcuts; pictorial narrative; graphic; interdisciplinary studies